Paratext in Performance: Live Poetry as a Direct Encounter between Poet and “Reader” - Novak, Julia (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Like its primary medium, language, poetry exists in two distinct forms: as written text and in oral performance. Nowadays, live poetry―poetry performed or “read” by the poet to a live audience, for instance at poetry readings, open mics, or poetry slams―constitutes an important mode of publication for poets, as well as a prominent mode of experiencing poetry for the “reader.” As such, live poetry entails a direct encounter and the physical co-presence of the poet―now cast in the double role of “poet-performer”―and the audience. This encounter takes place in a specific spatiotemporal situation, that is, as an “event,” a fact largely neglected in the methodologies traditionally applied to the study of poetry.